Outcomes of chair based exercise with progressive resistance training on physical performances among older adults: a preliminary study - Nor Afifi Razaob,; Nor Najwatul Akmal Ab Rahman,; Ain Efahera Ahmad Tajuddin,; Nor Azlin Mohd Nordin, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Enhancement of physical function had been shown in older adults who actively participate in physical activities, particularly in the form of aerobic training with addition of progressive resistance training (PRT). However, it is quite challenging and risky for most older adults to exercise in standing position without any support. Chair Based Exercise (CBE) is an alternative mode of exercise for older adult to facilitate exercise participation and increase safety. Its effect when combined with resistance training is unknown to date. Therefore, the aim of this study was to evaluate the outcome of CBE with PRT on physical performances among older adults. A total of 18 older adults (13 females (72%)) and 5 males (28%)), aged 60 to 83 years with mean age (SD) 72.67 (6.17) years completed the study. All subjects performed CBE with PRT intervention twice weekly for 8 weeks, with individually-tailored exercise progressions. Pre and post measurements of physical performance were performed using Six MinutesWalk Test (6MWT), Five Times Sit to Stand (FTSTS) and Hand Grip Strength (HGS) test. Significant improvement in 6MWT (p < .001), HGS Right hand (p = .043), HGS Left hand (p < .001), FTSTS (p < .001) was shown after the eight-week intervention. Adding PRT into seated exercises results in further improvement in physical performance of older adults. CBE-PRT may be recommended as an exercise routine for older adults living in the community.